2018
DOI: 10.1016/j.artd.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Dual-taper modular hip implant: Investigation of 3-dimensional surface scans for component contact, shape, and fit

Abstract: BackgroundThe etiology of wear particle generation and subsequent corrosion in modular total hip arthroplasty implants likely begins with mechanical fretting. The purpose of this study was to determine geometric features of the male and female taper surfaces that drive stability within the neck-stem junction.MethodsEighteen modular hip components received 3-dimensional surface scans to examine the neck-stem taper junction using an optical scanner. The normal distance between the surfaces of the neck taper as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In in vitro conditions, artificially contaminated taper junctions with porcine bone chips have created micromotions that are more than twice as large than those of clean taper junctions [ 92 ]. Some relative motion at the neck-stem junction occurs due to the shape of the tapers deviating from an ideal design dimension [ 93 ]. Three-dimensional contact colour maps clearly indicate that the surfaces are not in contact over the entire circumstances but typically at four localized lines of contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In in vitro conditions, artificially contaminated taper junctions with porcine bone chips have created micromotions that are more than twice as large than those of clean taper junctions [ 92 ]. Some relative motion at the neck-stem junction occurs due to the shape of the tapers deviating from an ideal design dimension [ 93 ]. Three-dimensional contact colour maps clearly indicate that the surfaces are not in contact over the entire circumstances but typically at four localized lines of contact.…”
Section: Discussionmentioning
confidence: 99%
“…Some implants also show one surface in contact or at closer proximity than the contralateral surface. The cause of the deviation in dimensions is most probably machine tool deflexion during machining [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of corrosion in the neck-stem junction has been debated. Some say that the shape of the neck-stem tapers may deviate from ideal dimensions causing relative motions between the neck and stem (Frisch et al 2018). Others state that corrosion occurs regardless of design and that the primary cause is mixed-metal couples with unequal modulus of elasticity (Young's modulus), allowing for increased metal transfer and surface damage (galvanic mode of corrosion) (Su et al 2017).…”
mentioning
confidence: 99%
“…Even though the authors have found the overall mean revision rate (3.95%) and the mean revision rate for fracture of the modular neck component (0.43%) for modular prosthesis acceptable, they consider modular prostheses to be a viable management option only in patients with considerable anatomical hip deformities that cannot be corrected with standard fixed-neck implants. The review also points out two national registry reports, which revealed that modular neck prostheses had a higher revision rate compared to traditional, fixed-neck prostheses in patients with osteoarthritis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with slight variation between implant position and offset, these dissimilarities could be responsible for different timing at which modular neck fracture occurred. However, Frisch et al have shown that the shape of the neck and stem tapers deviate from ideal design dimensions, contributing to relative motions between the neck and the stem and may place the implants at higher risk for failure [ 24 ]. This means that such catastrophic failures can occur unpredictively in otherwise normally functioning implant(s).…”
Section: Discussionmentioning
confidence: 99%